2019
DOI: 10.1016/j.jsps.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic, antioxidant, molecular docking and HPTLC analysis of miquelianin isolated from Euphorbia schimperi C. Presl

Abstract: The present study demonstrates the miquelianin or quercetin 3-O-glucuronide (compound 1) isolated from aerial parts of Euphorbia schimperi exhibited significant results for antioxidant and antidiabetic potential. The compound 1 along with kaempferol 3-O-glucuronide (compound 2) and quercetin 3-O-rhamnoside (compound 3) isolated from the same source were quantified by validated HPTLC method. Antioxidant activity was determined by chemical means in terms of ABTS radical cation and DPPH radical scavenging activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…In this study, the green mobile phase was obtained by the simple mixture of ethanol and water (green solvents) in comparison to the normal HPTLC method. The application of RP-HPTLC methods offer several advantages over normal phase HPTLC methods [ 37 , 40 ]. In addition, green RP-HPTLC methods for the simultaneous determination of 6-SHO and 6-GIN also reduce the toxicity of the proposed method to the environment [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the green mobile phase was obtained by the simple mixture of ethanol and water (green solvents) in comparison to the normal HPTLC method. The application of RP-HPTLC methods offer several advantages over normal phase HPTLC methods [ 37 , 40 ]. In addition, green RP-HPTLC methods for the simultaneous determination of 6-SHO and 6-GIN also reduce the toxicity of the proposed method to the environment [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it helped in avoiding the interference due to impurities in the chromatograms, formation of compact spot and detection clarity. 37 Eco-friendly RP-HPTLC method for the analysis of rivaroxaban will reduce the environmental toxicity caused by routine toxic solvents used in routine pharmaceutical analysis. 33,34 Our research work gave a very good analytical technique for the estimation of the rivaroxaban in NPs formulation.…”
Section: Methods Developmentmentioning
confidence: 99%
“…Recent research has shown that the major components in SC are miquelianin, quercetin 3- O -(2″- O - β-glucopyranosyl)-α-rhamnopyranoside, and quercitrin ( Nho et al, 2019 ). Miquelianin is the major consitutent of SC water-extract (11.75 ± 0.09 mg/g) and it has anti-inflammatory ( Nho et al, 2019 ), anti-oxidative, anti-diabetic ( Ahmed et al, 2019 ), and neuroprotective effects ( Yuan et al, 2017 ). Rutin is one of the most well-known herbal constituents and is used therapeutically for the suppression of atopic dermatitis ( Choi & Kim, 2013 ), and as an anti-asthmatic ( Jung et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%